Will gay men self-objectify based on communities' expectation of a traditional-masculine ideal? - Moseya, Ntsandeni (My University, 2024)
This study explored gay men’s viewpoints about their tendency to self-objectify based on societal expectations of what a masculine ideal ought to be. Q methodology was deployed to enable gay men to share their own perceptions of what a masculine ideal is, and at the same time engage in and share their self-perceptions of being gay. A concourse of 394 statements was produced from recorded interview sessions. Hegemonic masculinity and self-objectification frameworks were utilised to construct a matrix to be used to extract two Q samples (that is, final sets of statements), each consisting of 32 statements. Each Q sample was accompanied by a unique set of sorting instructions. The first Q sort instruction required gay men to sort statements according to how they perceived a masculine ideal. The second instruction required the same gay men to sort the statements according to the perceptions of themselves as gay. Two viewpoints were identified and interpreted: (1) the masculine ideal is considerate, masculine ideal is non-existent; and (2) self-appreciation, physical appearance contentment. Together, the results revealed that a masculine ideal is not perceived in relation to societal hegemonic masculine characteristics and beliefs; and the gay men perceived themselves as self-appreciative with no hints of selfobjectification tendencies. In contrast with the extant empirical evidence, the study found that gay men in traditional rural communities do not possess any form of selfobjectification tendencies.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2024
Keywords: Self-objectify; Societal expectations; Masculine ideal; Personal equation; Self esteem; Gay men; Masculine beauty (Aesthetics)